2009
DOI: 10.1136/ard.2009.110502
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor alpha blockade impairs dendritic cell survival and function in rheumatoid arthritis

Abstract: The data show that TNFalpha blockade has profound effects on DC function with downstream, potentially immunoregulatory, effects on T cells. These data provide an interesting new insight into the potential mechanism by which anti-TNFalpha drugs contribute to the restoration of immunoregulation in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 40 publications
10
39
0
Order By: Relevance
“…3C, 3D). Our data also support a report on the reduced survival of LPS-stimulated DCs after TNF neutralization (41). Similar data obtained with human plasmacytoid pre-DCs as well as murine macrophages highlight the general relevance of TLR-induced autocrine TNF for the survival of APCs (42,43).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…3C, 3D). Our data also support a report on the reduced survival of LPS-stimulated DCs after TNF neutralization (41). Similar data obtained with human plasmacytoid pre-DCs as well as murine macrophages highlight the general relevance of TLR-induced autocrine TNF for the survival of APCs (42,43).…”
Section: Discussionsupporting
confidence: 79%
“…Therapeutic targeting of DCs has been suggested in autoimmune diseases such as rheumatoid arthritis (59). Just recently, Baldwin et al (41) reported impaired DC maturation and also increased apoptosis after TNF blockade in vitro and in vivo, also supporting the model in which TNF appears as the central cytokine regulating DC survival. Beyond illustrating the important role of different levels of autocrine TNF in the context of microbial stimulation, our data now reveal a molecular mechanism linking the capacity of the cell to produce its autocrine survival factor to the regulation of the intrinsic pathway of apoptosis by the balance of pro-and antiapoptotic members of the BCL-2 family.…”
Section: Discussionmentioning
confidence: 85%
“…Autocrine TNF-a was previously shown to provide survival signals to DCs (20). Blocking of TNF-a with either soluble p55TNFR-Fc or anti-TNF-a mAb (infliximab) significantly reduced survival of LPS-matured DCs (31). We show in the present study that survival of Col-DCs was impaired by treatment with Enbrel, although to a much lower degree than by treatment with anti-OSCAR mAb.…”
Section: Discussionsupporting
confidence: 46%
“…Other studies reported on the direct effect of sulphasalazine on neutrophil apoptosis [176] or the role that monocytes play in the inhibition of glucocorticoid-mediated apoptosis in RA [177]. synoviocyte apoptosis have focused on those investigations in which RA patients have responded to these drugs in a clinically meaningful way [178][179][180][181][182].…”
Section: Apoptotic Responses To Anti-ra Therapiesmentioning
confidence: 99%